Analyzing the Perceived Benefits of LEED-Certified and Energy Star–Certified Buildings in the Realm of Local Economic Development. (November 2015) - Leland, Suzanne M.; Read, Dustin C.; Wittry, Michael
Data collected from a national survey of economic development professionals are used in this study to examine the perceived role of Leadership in Energy and Environmental Design–certified and Energy Star–certified buildings in the business recruitment process. A series of ordinal logistic regression models are estimated to examine economic developers' attitudes toward these buildings after controlling for their personal characteristics and the characteristics of the communities where they work. The results suggest less favorable perceptions about this form of sustainable real estate development in smaller communities and those with weaker economic fundamentals. Furthermore, women employed in economic development are found to have more favorable attitudes toward these buildings than their male counterparts. Increasing support for sustainable real estate development among economic developers working in local government may therefore require a combination of thoughtful policy making, executive education, and greater gender diversity in the profession.